Challenges faced by students in computer- and paper-based national examinations: the indonesian context - Basopi, Pegiawan; Abdul Aziz, Roslina; ., Haiyudi (GADING Journal for the Social Sciences, 2025)
The national examination (NE) is an evaluation system that begins from junior high school to senior high school in Indonesia. The Indonesian government has implemented computer-based tests (CBT) and paper-based tests (PBT) for the NE since 2014. The aim of this study is to investigate the challenges students faced in these examinations. The study adopted a qualitative approach to data analysis, involving semi structured interviews. Six high school graduates were selected as participants. The findings reveal that CBT presents 3 major challenges, namely unfamiliarity with computer hardware, increased anxiety due to the visible countdown timer, and fear of technical problems that may disrupt the exam. PBT presented issues such as poor-quality test papers, difficulties in correctly blackening answer sheets for Optical Mark Recognition (OMR), and time management problems resulting in stress and hasty responses. The study concludes that both CBT and PBT formats pose challenges to students’ optimal performance. These findings offer important insights for enhancing the design and delivery of national examinations in Indonesia, as elaborated further in the paper.